Rancangan Platform Galeri Bisnis Pada Inkubator Bisnis di Area Sub-Urban Dalam Meningkatkan Pemasaran UMKM - Nugroho, Tejo; Syaifullah; Sarvatilova R S, Virginia (Jurnal Manajemen dan Bisnis Kreatif, 2024)
Indonesia has the highest number SMEs in the ASEAN region. Employ 97% of theworkforce, contribute 60.3% to GDP and 14.4% of national exports. However, thecondition of Indonesian SMEs is still suboptimal, particularly in terms of access tofinancing and markets. This remains a major challenge for SMEs in expanding theirbusinesses. SME incubator gallery platform is one solution to enhance collaborationwith SME. Through this, SME can promote and market their products more widely andeffectively. The platform facilitates connections with potential partners such as suppliers,distributors, and investors, who can assist in business development and expansion. TheCanvas Business Lean method was employed in designing this platform. The outcomeof this research is the Incubator Platform, which SME can utilize to enhance theirbusiness competencies. To join this platform, SME participants register through theplatform and upon verification by the administrative team, they gain access to theprovided features.